Towards digitalization for comprehensive measurement of the bioeconomy: exploring the convergence between elements of the cyber-physical social system - Leavy, Sebastian (2026)
The bioeconomy is an evolving concept that faces measurement challenges due to the scarcity of up-to-date, structured, and comprehensive data. We argue that digital technologies—including artificial intelligence (AI), machine learning (ML), automation, sensors and biosensors, blockchain and the Internet of Things (IoT)—can enhance the bioeconomy measurement. However, there is currently no clear evidence linking the elements of the cyber-physical social system (CPSS) within the conceptual scopes of the bioeconomy. So, this study explores the convergence between digital technologies and the conceptual elements of bioeconomy. Firstly, independent literature reviews were conducted using Biblioshiny, VOSviewer, QDA Miner and WordStat to (i) define the core terms in the scope of bioeconomy concepts and (ii) map the digital technologies. Secondly, we coded and analyzed the literature content with QDA Miner and WordStat to examine the co-occurrence of digital technologies and the conceptual elements of the bioeconomy. The results indicate that the Biomass-Based Bioeconomy (BmBB), Biotechnology-Based Bioeconomy (BtBB), and Biosphere-Based Bioeconomy (BsBB) possess distinct clusters of conceptual elements but also integrative domains, like metabolism. Our findings reveal that digital technologies within categories of data science and analytics, computing and software, and imaging and sensing have been the most prevalent in the bioeconomy context. Evidence has surfaced regarding the interactions between the bioeconomy concepts and digital technologies, illustrating the role of digitization in enhancing data collection, storage, processing and communication across various aspects of the bioeconomy. This evidence underscores the potential of digitalization for a comprehensive measure of the bioeconomy. Ultimately, this research provides valuable insights for improving bioeconomy assessment and supports sustainability goals by integrating emerging digital technologies with the bioeconomy development.